Menggali Kompetensi Profesional Guru: Kunci Peningkatan Mutu Pendidikan - Layyana Syarifah Pane; Ade Irma; Memen Permata Azmi (Politeknik Kampar, 2025)
This study aims to explore the professional competence of teachers as a key factor in improving the quality of education at SMA Negeri 1 Tambang. The research employed interviews with an experienced teacher to gain insight into the strategies for developing professional competence in facing modern educational challenges. The findings indicate that professional competence encompasses not only subject mastery and classroom management but also communication skills, collaboration, and continuous self-development. Challenges such as administrative burdens and limited time hinder the optimal development of these competencies. Therefore, systematic support from schools and government, including ongoing training and adequate facilities, is essential. In conclusion, professional competence is a crucial foundation for creating a conducive learning environment and enhancing the overall quality of education.